Outlier sectors : areas of non-free trade in the North American Free Trade Agreement - Miller, Eric (IDB-INTAL Buenos AiresAR, 2002)
Identifies the areas of non-free trade in the North American Free Trade Agreement, and classifies them by primary source advocating protectionism i.e. producer interests or governments themselves. Analyzes the characteristics of each source. Examines the sectors that are subject to tariff phase-out periods and/or special mechanisms lasting beyond ten years - the baseline liberalization period. Focuses exclusively on trade in goods.